Experimental study of printed-circuit heat exchangers with airfoil and straight channels for optimized recuperators in nitrogen Brayton cycle. (5th January 2023) - Chung, Sungkun; Lee, Su Won; Kim, Namhyeong; Shin, Seong Min; Kim, Moo Hwan; Jo, HangJin
Highlights: The recuperator has been reported as the largest component in nitrogen Brayton cycles. The compactness and economics can be enhanced by adopting advanced channel shapes. Experiments of advanced channel shapes, such as airfoil and straight, were performed. New correlations for the airfoil channel were developed to design the recuperator. Optimal design results of recuperator were discussed in terms of flow channel shapes. Abstract: In this study, experiments with straight and airfoil channels of printed-circuit heat exchanger (PCHE) are conducted within a 3 % heat balance difference to investigate thermal–hydraulic performances for nitrogen (N2 ) Brayton cycle recuperator. The results reveal that the airfoil PCHE has higher heat transfer performance and pressure drop than the straight PCHE. In the case of straight PCHE, the Gnielinski correlation for heat transfer and Blasius correlation for pressure drop show sufficient predictability. For airfoil PCHE, new correlations for Nusselt number and friction factor are developed to predict the experimental data with a maximum error of 2 % for heat transfer and 8 % for pressure drop. Subsequently, the newly developed and other previous correlations for different channel configurations are used to compare the comprehensive performances. The results indicate that airfoil PCHE has the highest comprehensive performance rather than straight, zigzag, and S-shape PCHE channels under the given hydraulic diameter and pumping power conditions. With the validated PCHE 1-D code, the optimal volumes are calculated for target conditions considering the PCHE channel configuration effect. The design result of the airfoil type has the smallest volume compared with other PCHE channel types, which was almost 21 % reduced volume than that of zigzag PCHE.